(untitled) (West African Journal on Sustainable Development, 2024)
The solution or the way out to herders-farmers violent clashes or crisis in Nigeria has remained illusory due to lack of accord, mostly between the Federal Government of Nigeria and affected North-Central and Southern states Governments, regarding the right method for curbing the menace. This continuous lack of accord is attributable to the sentimentalization of this sensitive national issue given the wide ethnic and religious differences between two warring groups – the ‘herders’ who are mainly Muslims and Fulani, and the crop farmers who are predominantly Christians from the middle-belt and southeastern states. The mission of this study, therefore, is to identify any key stakeholder group that uses scientific methods devoid of sentiments to study any phenomenon before concluding fact-based findings. It is against this backdrop that this study tries to examine academics’ recommendations on the sustainable panacea to Herders-Farmers conflict in Nigeria. Because of the empirical nature of the study, it employed library-and-desk research methods for data collection. The population of the study constitutes journal articles on Herders-Farmers clashes in Nigeria. Twenty-eight papers were sourced and analyzed using content analysis. The study observed that the majority of the academics recommended conflict resolution mechanisms, mass orientation, and ranches as the sustainable solution to the constant herders-farmers crisis in Nigeria. The study, therefore, recommends that the ranches proposed by the Federal Government of Nigeria should be directed in some affected states to be able to assess its real potentials instead of totally rejecting it without subjecting it to any form of experimentation.